Structural basis for the regulation of L-type voltage-gated calcium channels: interactions between the N-terminal cytoplasmic domain and Ca2+-calmodulin - Liu, Zhihong; Vogel, Hans. J. (Frontiers in Molecular Neuroscience, 2012)
It is well known that the opening of L-type voltage-gated calcium channels can be regulated by calmodulin. One of the main regulatory mechanisms is CDI (calcium-dependent inactivation), where binding of apo-calmodulin (CaM) to the cytoplasmic C-terminal domain of the channel can effectively sense an increase in the local calcium ion concentration. Calcium-bound calmodulin can bind to the IQ-motif region of the C-terminal region and block the calcium channel, thereby providing a negative feedback mechanism that prevents the rise of cellular calcium concentrations over physiological limits. Recently, an additional Ca2+/CaM-binding motif (NSCaTE, N-terminal spatial Ca2+ transforming element) was identified in the amino terminal cytoplasmic region of Cav1.2 and Cav1.3. This motif exists only in Cav1.2 and Cav1.3 channels, and a pronounced N-lobe (Ca2+/CaM) CDI effect was found for Cav1.3. To understand the molecular basis of this interaction, the complexes of Ca2+/CaM with the biosynthetically produced N-terminal region (residues 1-68) and NSCaTE peptide (residues 48-68) were investigated. We discovered that the NSCaTE motif in the N-terminal cytoplasmic region adopts an α-helical conformation, most likely due to its high alanine content. Additionally, the complex exhibits an unusual 1:2 protein:peptide stoichiometry when bound to Ca2+-CaM, and the N-lobe of CaM has a much stronger affinity for the peptide than the C-lobe. The complex structures of the isolated N- and C-lobe of Ca2+/CaM and the NSCaTE peptide were determined by NMR spectroscopy and data-driven protein-docking methods. Moreover we also demonstrated that the CaBP1 protein, which competes with CaM for binding to the C-terminal cytoplasmic domain, binds only weakly to the NSCaTE region. The structures provide insights into the possible roles of this motif in the calcium regulatory network. Our study provides structural evidence for the CaM-bridge model proposed in previous studies.